Analisis Pengaruh Foreign Direct Investment (FDI), Penanaman Modal Dalam Negeri (PMDN), Infrastruktur Dan Pengangguran Terhadap Produk Domestik Regional Bruto (PDRB) Nusa Tenggara Barat 2021 – 2023 - Aini Daulay, Latipah; Irawan, Edi (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
Economic growth in a region is very important for assessing the success of development. Gross Regional Domestic Product (GRDP) is the main benchmark to determine the size of the economic output in the area, including in the province of West Nusa Tenggara (NTB). However, if we look at the development of NTB’s GRDP from 2021 to 2023, there have been many changes influenced by economic factors such as foreign direct investment (FDI), domestic investment (PMDN), infrastructure conditions, and unemployment rates. This study aims to analyze how these four factors affect the GRDP across regencies/cities in NTB. This research uses a quantitative method with data sourced from the Central Bureau of Statistics (BPS) and NTB Satu Data. The analysis uses panel data regression with EViews 12 software. The research results show that foreign direct investment (FDI) and domestic investment have a positive effect on GRDP, infrastructure also increases regional productivity, while unemployment decreases GRDP. Overall, all of these independent variables are significant in influencing NTB’s GRDP.